Muhallil marriage and marriage without a guardian consent / Balqis Mohd Ramli … [et al.] - Mohd Ramli, Balqis; Mohd Nazri, Nur Ainaa Azmina; Yahaya, Nurul Aunni; Roslan, Nur Zulaikha; Wan Ramli, Wan Nurain Afiqah (2023)
Marriage is one of the religious requirements that celebrates the inherent tendency of human beings to live in pairs. It is also something that is supported by the Quran and hadith, and the bond between husband and wife is regarded to be a blessing and a symbol of excellence. The Word of Allah S.W.T: ''And among the signs of His power is He created for you wives of your own kind, so that you feel at peace with him, and he made it among you feel love and affection Indeed in such a way it is true there are signs for people who think".